Gambaran Emotional Distress pada Siswa Sekolah Menengah Atas di SMA X Kabupaten Bekasi - Atmojo, Aristarkhus Dwi; Rahmi, Kus Hanna (YASIN, 2025)
Emotional distress is an individual's reaction when facing stressors (Bogoroch in deva & sofia 2014). describes emotional distress as mental or psychological trauma caused by tortious or non-tortious behaviour. The purpose of this study was to determine the description of emotional distress in students of SMAN 1 Babelan Bekasi. This study uses quantitative research methods with the type of correlation test research, validity and reliability to see if there are characteristics of emotional distress in students of SMAN 1 Babelan Bekasi. According to a researcher named (Kamaruddin, 2017) the research population is an area that includes objects or subjects that have certain quantities and characteristics and these conditions are determined by the researcher himself. In this study, the population to be studied is active students of SMAN 1 Babelan Bekasi with a minimum of 150 participants. This study involved students of SMAN 1 Babelan Bekasi who had an age of 15-18 years consisting of 75 women and 75 men. The sampling technique used by researchers is probability sampling with purposive sampling technique because this research focuses on determining the sample based on the researcher's consideration. Based on research conducted by researchers, it was concluded that a total of 268 students or participants with a presentation of 87 men and 181 women in class XII or at the final level at SMAN 1 Babelan experienced relatively low stress. So it can be concluded that the level of emotional distress in class XII at SMAN X Bekasi Regency is in the low category so that students have high awareness.